Sport-related traumatic injuries among schoolchildren (a questionnaire study) - Vlasta Merglova (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
Background: Childhood represents a risk period of susceptibility to sport-related injuries. Objectives: The aim of the study was to investigate the prevalence of sports-related injuries including orofacial traumas in children attending primary schools and participating in competitive sports, then to compare their situation with that of children engaging in sporting activities only at school and in their leisure time. The second aim of the study was concentrated on the use of sports mouthguards. Methods : Data was obtained by means of a questionnaire and statistically analysed by the basic statistic methods in Microsoft Office Excel and Pearson's chi-square test , and a statistical significance level p < 0.05 was established. Results: 341 children (175 girls and 166 boys) completed the questionnaires and 204 (59.8%) of them were competitive athletes. 146 (42.8%) children reported sports-related injuries and 47 (13.8%) children registered trauma of the orofacial region. Only 10 (2.9%) children regularly use sports mouthguards. No statistically significant differences were detected in the occurrence of sport-related injuries including orofacial traumas between the competitive athletes and non-competitive children. Conclusion: Sport-related trauma represents a risk not only for children engaging in competitive sport activities but also for children doing sports at school and occasionally in their free time.